2015
DOI: 10.1002/ana.24409
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal bands predict multiple sclerosis in children with optic neuritis

Abstract: We retrospectively evaluated predictors of conversion to multiple sclerosis (MS) in 357 children with isolated optic neuritis (ON) as a first demyelinating event who had a median follow-up of 4.0 years. Multiple Cox proportional-hazards regressions revealed abnormal cranial magnet resonance imaging (cMRI; hazard ratio [HR] = 5.94, 95% confidence interval [CI] = 3.39-10.39, p < 0.001), presence of cerebrospinal fluid immunoglobulin G oligoclonal bands (OCB; HR = 3.69, 95% CI = 2.32-5.86, p < 0.001), and age (HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 20 publications
4
43
1
Order By: Relevance
“…[17][18][19][20] IgG OCBs are more common in children with MS than in those with ADEM or other diseases mimicking MS. [17][18][19]21 Presence of IgG OCBs combined with an abnormal MRI was associated with a .26-fold hazard ratio for developing MS in children presenting with incident ON. 22 CSF IgM OCBs can also be found in a subset of patients with pediatric-and adult-onset MS. In adults their presence has been associated with more active/ aggressive disease, 23 but such an association has not been established in pediatric MS. 24 Of note, CSF exhibits age-related changes independent of MS disease mechanisms, particularly around puberty.…”
Section: General Aspects Of Cns Inflammatory Demyelinating Diseases Mmentioning
confidence: 98%
“…[17][18][19][20] IgG OCBs are more common in children with MS than in those with ADEM or other diseases mimicking MS. [17][18][19]21 Presence of IgG OCBs combined with an abnormal MRI was associated with a .26-fold hazard ratio for developing MS in children presenting with incident ON. 22 CSF IgM OCBs can also be found in a subset of patients with pediatric-and adult-onset MS. In adults their presence has been associated with more active/ aggressive disease, 23 but such an association has not been established in pediatric MS. 24 Of note, CSF exhibits age-related changes independent of MS disease mechanisms, particularly around puberty.…”
Section: General Aspects Of Cns Inflammatory Demyelinating Diseases Mmentioning
confidence: 98%
“…CSF examination, to detect intrathecal IgG synthesis, is not formally included among diagnostic criteria, nevertheless it can give an additional considerable contribution for diagnosis in patients at their first clinical episode, in addition to MRI [29,72,73].…”
Section: Clinical Aspects: How Similar To Adult Ms?mentioning
confidence: 99%
“…Two recent studies, one including patients with ON at presentation, the other one including patients with ADS, have shown that OBs are linked to a higher risk of subsequent MS, in addition and independently from the presence of lesions at brain MRI [72,73].…”
Section: Differential Diagnosis: Can Clinical Manifestations and Ancimentioning
confidence: 99%
“…CSF oligoclonal bands were found in 80% of pediatric patients with MS and in only 15% of children with monophasic ON. 30 Twenty-six percent of patients with adult MS and 42%-58% of patients with NMO may initially present with ON alone or in combination with other neurologic deficits. 31,32 Although young children may have bilateral severe ON without experiencing recurrence, given the importance of treatment to prevent irreversible visual disability in NMOSD and the high association of serologic markers such as ANA and anti-Ro/SSA with NMOSD, severe bilateral ON, poor response to steroids, or the presence of brain or spinal cord MRI findings typical of NMOSD should lead to evaluation of serum for AQP4 antibodies and concomitant autoantibodies.…”
Section: Neurology 87 (Suppl 2) August 30 2016 S55mentioning
confidence: 99%